Capacity building of women farmers organizations in the local fabrication and operation of GEM parboiler - Diabate, Fatoumata; Mujawamariya, Gaudiose; Dossou-Yovo, E. R (2024)
This report highlights the capacity-building efforts for women farmers' organizations on the local fabrication and operation of GEM parboiler technology under the AICCRA project. In 2024, 260 women from six rice parboiling organizations across five sites (Ségou, Niono, Sikasso, Sélingue, and Baguineda) received training to enhance their technical and soft skills in using GEM technology. The training covered key topics such as the benefits of rice parboiling, the state of parboiling in Sub-Saharan Africa, and the operation of GEM equipment. The technology addresses challenges like limited access to affordable firewood, smoke exposure, burns, and excessive labor. By adopting GEM, participating women saw a significant income increase of USD 200 per ton of parboiled rice and reduced firewood costs from USD 18.3 to USD 6.4 per ton. Moreover, the time needed to parboil 100 kg of rice was reduced from 1.5 hours to under 30 minutes. GEM technology has proven to be a transformative, gender-sensitive solution, empowering women farmers economically and improving their working conditions.